Konstruksi Makna Toleransi Pada Individu Dengan Tingkat Openness Berbeda - Astri Aroma; Sri Nurhayati Selian (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the construction of the meaning of tolerance among individuals with varying levels of openness to experience. Tolerance, as a fundamental value in a multicultural society, is understood not only as an acceptance of differences but also as an active process involving understanding, empathy, and openness to diversity. This study used a qualitative approach with a phenomenological design to explore individuals' subjective experiences in interpreting tolerance. Subjects were selected through purposive sampling, with 3 participants with high and low levels of openness identified using the Big Five Inventory-2 (BFI-2). Data collection involved in-depth interviews, observation, and documentation, while thematic analysis was used. The results show that individuals with high levels of openness interpret tolerance as an active, inclusive, and reflective attitude involving dialogue, empathy, and involvement in diverse social interactions. Conversely, individuals with low levels of openness tend to interpret tolerance as a passive attitude oriented toward conflict avoidance and maintaining social distance. These differences are also evident in the individuals' social behavior, cognition, and social experiences. Individuals with high openness demonstrate greater flexibility of thought and broader social experiences, while those with low openness tend to have more rigid thought patterns and limited social experiences. These findings suggest that tolerance is a construct of meaning influenced by an individual's personality and social experiences. Therefore, developing tolerance in education needs to consider personality aspects and provide diverse social experiences so that the value of tolerance can be internalized more deeply and meaningfully.